Fractional Dynamics of Individuals in Complex Networks - Turalska, Malgorzata; West, Bruce J. (Frontiers in Physics, 2018)
The dependence of the behavior of a single individual on the global dynamics of the social network to which it belongs is an open problem in sociology. We demonstrate that for a dynamical network belonging to the Ising universality class this problem can be approached analytically through a subordination procedure. The analysis leads to a linear fractional differential equation of motion for the average trajectory of the individual, whose analytic solution for the probability of changing states is a Mittag-Leffler function. Consequently, the analysis provides a linear description of the average dynamics of an individual, without linearization of the complex network dynamics.